2021
DOI: 10.3390/ma14051111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Concentrations of NaOH on the Inter-Particle Gelation of a Fly Ash Geopolymer Aggregate

Abstract: Aggregates can be categorized into natural and artificial aggregates. Preserving natural resources is crucial to ensuring the constant supply of natural aggregates. In order to preserve these natural resources, the production of artificial aggregates is beginning to gain the attention of researchers worldwide. One of the methods involves using geopolymer technology. On this basis, this current research focuses on the inter-particle effect on the properties of fly ash geopolymer aggregates with different molari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…The unreacted spherical particles clearly could be visualised in Figure 2 . This was also in accordance with the results published by Alida et al [ 21 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The unreacted spherical particles clearly could be visualised in Figure 2 . This was also in accordance with the results published by Alida et al [ 21 ].…”
Section: Resultssupporting
confidence: 94%
“…The unreacted spherical particles clearly could be visualised in Figure 2. This was also in accordance with the results published by Alida et al [21]. As can be observed in Figure 7, the microstructure displayed the crystalline grains structure after the geopolymer sintered at 900 °C.…”
Section: Electrical Conductivitysupporting
confidence: 92%
See 1 more Smart Citation
“…At present, the most widely used aluminosilicate materials in alkali-activated gel materials are fly ash and metakaolin. Studies have shown that alkali-reactive material concrete has excellent strength, corrosion resistance, fire resistance, and durability, and it can replace Portland cement as a concrete adhesive [24][25][26]. Therefore, alkali excitation technology is expected to become an important part of sustainable by-products.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it will have a serious impact on the ecological environment [ 4 ]. At present, it has been reported that industrial solid wastes such as fly ash (FA) [ 5 ], ground granulated blast furnace slag (GGBFS) [ 6 ], and steel slag [ 7 ] are used to prepare aggregates to replace some natural aggregates in concrete. It can not only slow down the mining of natural aggregates but also reduce environmental pollution.…”
Section: Introductionmentioning
confidence: 99%